Uporaba bralno-učnih strategij pri pouku slovenskega jezika v 4. razredu v sodelovanju s knjižničarko - Purg, Mojca (Šolska knjižnica, 2016)
When starting school, students have very different prior knowledge and particularly pre-reading habits. How to develop them to the point that students are able to learn independently, is a dilemma which we at Hajdina Primary School faced in 2011. In cooperation with the National Education Institute Slovenia, we became involved in the project Empowering Students through Improving Reading Literacy and Access to Knowledge (Reading Literacy - RL in short), which was partially financed by EU funds. The National Education Institute Slovenia, the Maribor unit, was in charge of coordination and provided great support. Teachers prepared an action plan and, in addition to the mastering of reading habits, we also tackled the incorporation of reading strategies into lessons. In the process, we prepared classroom observations for one another, which were also attended by the counsellors of the National Education Institute Slovenia, and the teachers and principals of the schools participating in this project.
Keywords: bralna pismenost; branje; knjižnično informacijsko znanje; osnovne šole; razredni pouk; slovenščina; učne metode